Therapeutic education process at An Islamic Hospital in South Kalimantan, Indonesia - Taufik Hidayat; Mahyuddin Barni; Agus Setiawan (Intelektual Pustaka Media Utama, 2022)
This study aimed to determine the effect of Islamic interpersonal competence integrity as a therapeutic education process on healing motivation. Researchers used Sequential Explanatory Designs as a research design. The respondets were Muslim patients who received inpatient services at the Banjarmasin Islamic Hospital. Subjects were 147 patients who were taken sequentially using a consecutive sampling technique. Researchers used Chi-square inferential statistical tests and Logistic Regression tests in quantitative analysis, while in qualitative analysis, researchers used Taxonomic analysis. The results of the Chi-square analysis showed that there is a significant relationship between each aspect of Al-Luthfu (hospitality), Al-Adab (politeness), Al-'Uthfu (gentleness in the form of attention), and As-Shabru (patience) with healing motivation. The results of the Logistics Regression analysis showed that simultaneously there was a significant effect on aspects of Al-Luthfu, Al-'Uthfu, and As-Shabru on healing motivation. Qualitatively, the process of implementing Islamic interpersonal competence integrity education considers the patient's level of anxiety, stress level of chronic illness and avoids patient discomfort to nurses. This study suggested to nurses of Banjarmasin Islamic Hospital to build a commitment to serve patients by prioritizing aspects of As-Shabru, building Islamic-based communication, increasing educational competence, and understanding patient characteristics.